2020
DOI: 10.11144/javeriana.upsy19.cfai
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analysis of the Invalidating Childhood Environment Scale in Spanish (ICES)

Abstract: Background/Objective: The Invalidating Childhood Environment Scale (ICES) is an instrument designed to assess retrospectively parental invalidation experience, according to Marsha Linehan’s definition of invalidation. The main aim of this paper is to determine the factorial structure of the ICES. Three factor structures: Standard Model, Reduced Model, and 2 Factor Model are examined. Also, the association between invalidating experience and borderline symptoms is studied. Method: Data from a non-clinical, volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Moreover, CFAs performed on a clinical sample of individuals with eating disorders (ED) suggested that the data were better represented by the two-factor model as opposed to the one-factor model. The two-factor and one-factor models obtained in our study were aligned with the models obtained in other studies, such as the model obtained in the USA ( 15 ), the CFA used in the French version ( 16 ), the model obtained in the Portuguese version ( 17 ), and the model established in the Spanish version ( 19 ). These studies demonstrate that the ICES factor structure is consistent among Western cultures.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Moreover, CFAs performed on a clinical sample of individuals with eating disorders (ED) suggested that the data were better represented by the two-factor model as opposed to the one-factor model. The two-factor and one-factor models obtained in our study were aligned with the models obtained in other studies, such as the model obtained in the USA ( 15 ), the CFA used in the French version ( 16 ), the model obtained in the Portuguese version ( 17 ), and the model established in the Spanish version ( 19 ). These studies demonstrate that the ICES factor structure is consistent among Western cultures.…”
Section: Discussionsupporting
confidence: 75%
“…To the best of our knowledge, psychometric properties of the ICES have been assessed exclusively in the United States (maternal invalidation alpha = 0.90; paternal invalidation alpha = 0.88) ( 15 ), France (maternal invalidation alpha = 0.84; paternal invalidation alpha = 0.87) ( 16 ), Portugal (non-clinical sample alpha = 0.912; clinical sample alpha = 0.932) ( 17 ), Turkey (maternal invalidation alpha = 0.84; paternal invalidation alpha 0.87) ( 18 ), and Spain (maternal invalidation alpha = 0.83; paternal invalidation alpha = 0.83) ( 19 ). The factor structure of the scale has demonstrated inconsistent results.…”
mentioning
confidence: 99%
See 1 more Smart Citation